2009
DOI: 10.1590/s1677-04202009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis and photosynthetic performance of improved papaya genotypes

Abstract: Brazil is the largest world producer of papaya and the third largest exporter despite of only 1.5 to 2.0% of its production is exported. Such an underexplored exportation potential highlight the necessity for physiological studies on new cultivars and hybrids to verify their agronomic and commercial viability. Two Brazilian states, Bahia and Espirito Santo, are responsible for 80% of national production. Papaya can also be an agricultural alternative to north / northeast of Rio de Janeiro, because the region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Nonetheless, the higher g s and E , together with similar A net values of Golden compared to Sunrise Solo leaves resulted in reduced iWUE and WUE [see Supporting Information—Table S2 ] . Lower WUE confirm earlier results (Torres-Netto et al 2009), and could also be related to observed lower chlorophyll content. In soybean, reduced pigmentation in mutants linked to increase in g s and reduced iWUE and integrated canopy WUE (Slattery et al 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, the higher g s and E , together with similar A net values of Golden compared to Sunrise Solo leaves resulted in reduced iWUE and WUE [see Supporting Information—Table S2 ] . Lower WUE confirm earlier results (Torres-Netto et al 2009), and could also be related to observed lower chlorophyll content. In soybean, reduced pigmentation in mutants linked to increase in g s and reduced iWUE and integrated canopy WUE (Slattery et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The principal producers were India (5.69 million t from 133 000 ha), Brazil (1.42 million t from 30 372 ha), Mexico (0.95 million t from 16 820 ha) and Indonesia (0.90 million t from 9980 ha) (FAOSTAT 2016). Although Golden fruits are better accepted by consumers worldwide due to the superior appearance of the fruits, greater transport resilience and longer post-harvest, Golden plants are less vigorous (Torres-Netto et al 2009; Castro et al 2014) and lower yielding compared to ‘Sunrise Solo’ (90 vs. 120 t ha −1 in the whole cycle) (Caliman Agrícola, Linhares, Espiríto Santo, Brazil, pers. comm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll fluorescence (Fv/Fm) parameter is normally used to evaluate stress on the metabolism of the plant (Evlard et al, 2014;Linger et al, 2005). And, any alteration in the plant photosystem (where protein is involved in photosynthesis) highlights impairment in the photosynthetic process (Torres Netto et al, 2009). Misra et al (2012) found that Fv/Fm value between 0.78-0.84 indicates fitness of a plant.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, in a comparison of five different genotypes in Brazil, one cultivar (Golden) was identified, which, during the middle of the day, had stomatal conductance (and transpiration rates) higher than other four genotypes. However, over the 12-week period of measurements, photosynthetic rates were similar for all five genotypes (Torres-Netto et al ., 2009). In a similar comparison of five cultivars in South India, one (Co7) stood out from the others in many of the attributes measured in the field during the summer months, including gaseous exchange processes, cell membrane integrity and various chlorophyll indices.…”
Section: Plant Water Relationsmentioning
confidence: 99%